Best Answer

y = x2 + 6x + 7

a = 1, b = 6, c = 7

Since a is positive, the graph opens upward. You can find the vertex coordinates (-b/2a, f(-b/2a)) = (-3, f(-3)) = (-3, -2), draw the axis of symmetry, x = -b/2a = -3, plot the y-intercept point (0, 7), plot the point (-b/a, 7) = (-6, 7), and draw the graph that passes through these points.

Or complete the square.

y = x2 + 6x + 7

y = x2 + 6x + 9 - 9 + 7

y = (x2 + 6x + 9) - 2

y = (x + 3)2 - 2

So start with the graph of y = x2 whose vertex is at the origin. Move it 3 units to the left, and 2 units down.

Q: How to Graphs Y equals x2 plus 6x plus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

one

(3, -21)

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

(x-5)(x+11)

Related questions

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

one

(3, -21)

y â‰¥ 11

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}

(x-5)(x+11)

2x+6x=-9 => 8x=-9=> x=-8/9

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4